2021
DOI: 10.1039/d0cp03317k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactions on surfaces for applications in catalysis, gas sensing, adsorption-assisted desalination and Li-ion batteries: opportunities and challenges for surface science

Abstract: Chemical reactions on surfaces of innovative materials have direct implications in application fields, such as catalysis, batteries, gas sensing and desalination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 170 publications
0
15
0
Order By: Relevance
“…The variation of the current density (mA cm −2 ) on SCISO105 was high, which was changed from (3.32 × 10 −6 to 5.09 × 10 −7 ) mA cm −2 , which indicated that SCISO105 showed a strong surface reaction between the gas and the WE. 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation of the current density (mA cm −2 ) on SCISO105 was high, which was changed from (3.32 × 10 −6 to 5.09 × 10 −7 ) mA cm −2 , which indicated that SCISO105 showed a strong surface reaction between the gas and the WE. 26…”
Section: Resultsmentioning
confidence: 99%
“…The variation of the current density (mA cm À2 ) on SCISO105 was high, which was changed from (3.32 Â 10 À6 to 5.09 Â 10 À7 ) mA cm À2 , which indicated that SCISO105 showed a strong surface reaction between the gas and the WE. 26 Compared with the CO 2 gas purging condition, the current density variation of the WE was less in the O 2 gas purged reactor system, which indicated that the SCISO ternary nano- composite showed more sensing ability for the CO 2 gas. In the CV profile of SCISO101 and SCISO103, the positive current density values were (7.84 and 7.76) Â 10 À3 , and SCISO105 showed 3.17 Â 10 À6 mA cm À2 .…”
Section: Gas Sensing and Electrochemical Performance Testsmentioning
confidence: 93%
“…To get more insight into the nature of the catalytic activity, PA was applied (see eqn (1)). The results are shown in Table 6.…”
Section: Chemical Reactions On Faujasite Zeolitementioning
confidence: 99%
“…Adsorption and catalysis on crystal surfaces and in porous materials are of paramount importance to industry, related to fabrication of devices, storage and industrial production of many materials. 1 From the theoretical view point, describing chemical reactions is most naturally done with a quantummechanical (QM) approach, although there are some force fields capable of treating chemical reactions, 2 and a variety of hybrid methods combining molecular mechanics and QM (QM/MM). 3 Zeolites are important green catalysts used in many practical applications, [4][5][6][7][8][9][10][11] because guest molecules can easily penetrate into pores in these materials, which have many active sites inside.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2D ultrathin metal oxide (such as Co 3 O 4 , Rh 2 O 3 , ZnO, TiO 2 , WO 3 , SnO 2 , and so forth) nanosheets with a microscopic level of thicknesses have been considered as advanced catalytic materials for heterogeneous catalytic reactions because of their improved catalytic activity and stability. 26 − 29 Among the synthetically demanding 2D metal oxide nanomaterials, scrutinyite tin(IV) oxide with the orthorhombic crystal structure plays an important role in various applications because of its low electrical resistivity (10 –4 –10 –3 Ω cm), high sensitivity to atmospheric gas pollutants such as CO, CH 4 , N x O, and so forth, improved capacitance by combining with other phases, and so on. 30 − 33 Normally, under ambient temperature and pressure, SnO 2 forms its most stable tetragonal rutile-type crystal phase.…”
Section: Introductionmentioning
confidence: 99%